2022
DOI: 10.3389/fnut.2022.843076
|View full text |Cite
|
Sign up to set email alerts
|

Disparity of Gut Microbiota Composition Among Elite Athletes and Young Adults With Different Physical Activity Independent of Dietary Status: A Matching Study

Abstract: ObjectiveThis study aimed to investigate the disparity of gut microbiota among elite athletes and young adults with different physical activity independent of dietary status.MethodsIn Hangzhou, China, an age and sex matching study was conducted between April and May 2021. A total of 66 Chinese young adults were recruited in this study and divided into an elite athlete group, physically active group, and physically inactive group. Fecal samples were collected to assess gut microbiota composition. Dietary status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 68 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…Seventeen studies reported significant associations between PA 38,41,72,8385,43,44,59,63,6568 or SB 48,64,70 and microbial diversity (i.e., alpha- and/or beta-diversity), and 19 studies found significant differences in the relative abundance of specific bacteria in active vs . inactive participants 36,38,63,66,6871,78,84,85,39,41,42,4446,48,59 ( Table 2 ). Sixteen studies found significant differences in microbial diversity 47,49,62,7476,79,80,51,52,5458,61 and 13 in the abundance of specific microbial taxa 47,52,78,79,104,53,5558,7476 between athletes vs .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies reported significant associations between PA 38,41,72,8385,43,44,59,63,6568 or SB 48,64,70 and microbial diversity (i.e., alpha- and/or beta-diversity), and 19 studies found significant differences in the relative abundance of specific bacteria in active vs . inactive participants 36,38,63,66,6871,78,84,85,39,41,42,4446,48,59 ( Table 2 ). Sixteen studies found significant differences in microbial diversity 47,49,62,7476,79,80,51,52,5458,61 and 13 in the abundance of specific microbial taxa 47,52,78,79,104,53,5558,7476 between athletes vs .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the exposure, 26 cross-sectional studies recorded PA using self-reported questionnaires 36,37,46,48,59,6568,7072,38,73,78,81,8385,39–45 , whereas 8 studies included PA data registered by accelerometry 42,48,63,66,69,82,84,85 ( Table 2 ). Additionally, four studies reported SB data expressed as time per sedentary breaks/bouts or screen time 48,64,70,73 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the concept of “athletic microbiome” ( Barton et al, 2018 ; Mohr et al, 2020 ) has been introduced. Whereas some reviews have synthesized current state-of-art concerning endurance exercise ( Mach and Fuster-Botella, 2017 ) and competitive sports ( Wegierska et al, 2022 ), to the best of our knowledge, there exists no review specifically addressing the potential role of microbiomics for swimmers, since each sports discipline requires a specific set of techniques, training protocols, and interactions with the athletic infrastructure/facility (in this case, the swimming pool) ( Xu et al, 2022 ). Research has shown that swimming can exert a plethora of regulatory effects on the microbiome, in terms of immunometabolic and neuroimmunological ones, as demonstrated by a number of animal studies ( Huang et al, 2019 ; Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cells associated with the human body are more common than human cells (~100 trillion) [3]. More than 1000 bacterial species may be found in the intestines of each person, and over 70% of the total human microbiome is contained in the gut [4]. Whereas human cells are slowly replaced with identical (or nearly identical) copies, the cells of the gut microbiome are constantly changing due to immigration, emigration and differential rates of division based on the dynamic gut environment, to which they are much more sensitive and responsive than human epithelial cells.…”
Section: Introductionmentioning
confidence: 99%